2014
DOI: 10.1089/acm.2014.0216
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Complementary and Alternative Medicine Use Across Cancer Treatment and Relationship to Stress, Mood, and Quality of Life

Abstract: Objectives: Complementary and alternative medicine (CAM) use is prevalent, but specific use of CAM across cancer treatment is underinvestigated. The objectives of this study were to assess changes in CAM use across cancer treatment; specific reasons for and satisfaction with specific types of CAM used; and associations of CAM use with stress, mood, and quality of life (QOL) in women with newly diagnosed breast cancer. Design and setting: Seventy-seven women with early-stage breast cancer who underwent active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
0
24
0
3
Order By: Relevance
“…Our data also suggest that religious patients are more interested in CAM therapies since they might seek more integrative/ holistic approaches. Kang et al [24] showed that CAM use was highly prevalent in women with breast cancer throughout the cancer treatment. Prayer was the most common CAM; it had the highest satisfaction rates.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Our data also suggest that religious patients are more interested in CAM therapies since they might seek more integrative/ holistic approaches. Kang et al [24] showed that CAM use was highly prevalent in women with breast cancer throughout the cancer treatment. Prayer was the most common CAM; it had the highest satisfaction rates.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…While there is a movement toward incorporation of complementary care to improve psychological health in patients with cancer, few evidence-based methods exist to monitor the impact these interventions have on subjective health. 3233 …”
Section: Discussionmentioning
confidence: 99%
“…In Western society, more than 50% to 60% of CAM use is prayer or mindfulness meditation and about 10% use herbal products—suggesting the consideration of nonpharmacological approach to integrative oncology. 3 , 19 In contrast, more than 50% to 70% of patients in China and one-third in Taiwan received co-prescriptions of Chinese herbs to treat their breast cancer, with no awareness of potential herb-drug interaction. 9 , 10 There is evidence that many Chinese herbal extracts might upregulate ERα and HER2 gene expression in vitro 20 , 21 and interact with tamoxifen in vivo .…”
Section: Discussionmentioning
confidence: 99%